The effects of platform beveling on flake variation. (December 2017) - Leader, George; Abdolahzadeh, Aylar; Lin, Sam C.; Dibble, Harold L.
Abstract: There are many ways by which knappers can influence the morphology of the flakes they produce. This article presents the results of a set of controlled experiments designed to isolate and describe the effects of platform beveling, or the removal of material from either the exterior portion of platform surface or laterally adjacent to it. We show that there is a relationship between various aspects of flake morphology, including both size and shape, and the location, shape, and depth of bevels. These results, which are supported by analyses of archaeological materials, have implications for understanding how past knappers manipulated their cores in order to achieve specific results.